Reply to the letter on “Brazilian guidelines for the management of tuberculosis infection in immune-mediated inflammatory diseases: is retesting in latent tuberculosis screening appropriate and safe?” - de Souza, Viviane Angelina; Caparroz, Ana Luiza Mendes Amorim; Trevisani, Virginia Fernandes Moça; Tavares, Anna Carolina Faria Moreira Gomes; de Melo, Ana Karla Guedes; Trajman, Anete; de Medeiros-Ribeiro, Ana Cristina; de Medeiros Pinheiro, Marcelo; Xavier, Ricardo Machado; Monticielo, Odirlei Andre; de Resende Guimarães, Maria Fernanda Brandão; Sztajnbok, Flavio; et al. (Springer Nature, 2025)
In response to a letter addressing the Brazilian guidelines for tuberculosis infection (TBI) screening in immune-mediated inflammatory diseases (IMID), we clarify that the recommendations reflect a structured, evidence-based consensus developed by a multidisciplinary panel, in accordance with internationally accepted standards. We reaffirm the rationale for annual TBI retesting during the first three years of immunosuppressive therapy, particularly with TNF inhibitors, and the outweighed risk of tuberculosis preventive treatment (TPT), given the benefits. These recommendations are aligned with national and international public health policies and underscore the need for flexibility in clinical judgment. Nonetheless, they are conditional, reflecting the limited robustness of the available evidence. Continued dialogue is essential to ensure the safety and protection of IMID patients in high-burden settings like Brazil.